THE CURRENT LEVEL OF IMPLEMENTATION OF ICT IN THE LIFE OF SCHOOLS - Milan, KLEMENT (Trends in education, 2016)
Information and communication technologies now provide a variety of opportunities for improvement of the educational process. Therefore, they are coming to the forefront of teachers who thus face new challenges and on whom new demands are placed. They have to be ready not only to use modern didactic resources and technology, but also to create suitable teaching materials, and apply the later in classes.The widely proclaimed need of the involvement of new media and new education technologies in the educational process thus represents a precondition of further development of both pedagocial science and practice. Along with the promotion of new teaching techniques and methods derived therefrom, it is necessary to monitor the state and the level of implementation of ICT into the life of schools. The authors of the submitted paper are not aware of the existence of current overall analysis dealing with the issue. That is why they decided to map the current state of implementation of modern didactic means and tools of ICT at selected primary and secondary schools. The submitted paper presents the preparation, processing, and outputs of the investigation research, conducted by means of the module Profil Skola21.
Keywords: information and communication technology in school; innovation in education; modern teaching materials; school evaluation; module Profile School21.